Isolation and diagnosis of bacteria found in frozen beef imported in the city of Mosul - Walaa AbdulWahed Aljowady; Saba Abdulrahem Hassan; Hithem Abdulalla Rjab (College of Education for Pure Sciences, 2009)
ABSTRACT The aim of this study was isolation and identification of the bacterial presence in imported beef frozen meat. The study included examination of (60) beef frozen meat samples in the period between Feb.-Jun. 2007. The samples were collected from the shops in Mosul city. A total of 1(1.66%) Corynbacterium ranle isolates was obtained. 2 (3.33%) Corynhacterium pyogenis was obtained. 5(8.33%) E. coli was obtained, 10(16%) Proteus vulgaris was obtained, 1(1.66%) Proteus mirabilis, was obtained, 9(15%) Budvicia aquatica was obtained, 1(1.66%) Citrobacter diversns, 2(3.33%) Salmonella enteritidis, 1(1.66%) Arizona, 1(1.66%) Serratia marcescens, 1(1.66%) Edwardsiella tarda. 2(3.33%) Edwardsiella ictaluri, 2(3.33%) Pasteurella muttocdia, 1(1.66%) Pasteurella acrogenes 3(5%) Morganella, 2(3.33%) Staphylococcus aureus, 2(3.33%) Bacillus cerus, 1(1.66%) Pseudomonas, 1(1.66%) Yersinia enterocoli 2(3.33%) Klebsilla pneumonia was obtained. The samples transported to lab. and each sample was put in 15 ml of buffer peptone water and shaked for five minutes then (1-2) ml of each sample was transported to 10 ml of the (2) type of enrichment broth. The first Tetrathionate broth which contained iodine solution and incubated in 42 C for 48 hours. The second broth was Brain heart infusion broth and the samples incubated in (37 C) for 24 hours, and then the sampls transported inculated in Tetrathionate broth to Salmonella-Shigella agar and incubated in 37 C for (24) hours and the samples which were inculated in brain heart broth transported to Macconcy agar, blood agar and Nutrient agar and incubated in 37 for 24 hours, the study conducted several biochemical tests including citrate, urea, methyl red, indol, Voges-Proskaure, Triple iron sugar. Coagulation test, and incubated the tubes in 37 C for 24 hours, except Voges-Proskaure which incubated in 37 C for 48 h. The antibiotics sensitivity test was also carried out for many types of antibiotics such as (Tetracycline, Chloramphenicol, Ampicillin, amoxcycillin, Gentamycin, Erythromycin, Ciprofloxcin).